[Fol. 01b verso] - (:unkn) unknown (My University, 1722)
[Former shelf mark Q.5.12] --- Rev Questeborne was domestic chaplain to the Earl of Galway, and vicar of Burnchurch, co Kilkenny, 1716-29. TCD MS 2207 is also by his hand.
A true collection of severall letters on various subjects & c. written by severall persons and on various incidents
Keywords: Plantation records; Cartography; Ireland ?- History -- 18th century; Plantations -- Ireland; Cork (Ireland : County); Munster (Ireland); Maps 1720-1730